Cover Feature: Electroanalysis of Pharmaceuticals on Boron‐Doped Diamond Electrodes: A Review (ChemElectroChem 9/2019). Issue 9 (16th April 2019) - Sousa, Camila P.; Ribeiro, Francisco W. P.; Oliveira, Thiago M. B. F.; Salazar‐Banda, Giancarlo R.; de Lima‐Neto, Pedro; Morais, Simone; Correia, Adriana N.
Abstract : The Cover Feature shows how the boron‐doped diamond electrode exhibits a plethora of favorable properties for the electroanalysis of pharmaceuticals. The boron doping level and the applied electrochemical pretreatment have a marked effect on its performance. More information can be found in the Review by C. P. Sousa et al onpage 2350 in Issue 9, 2019 (DOI:10.1002/celc.201801742 ).